2021
DOI: 10.3389/fcell.2021.687524
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CRNDE Promotes ATG4B-Mediated Autophagy and Alleviates the Sensitivity of Sorafenib in Hepatocellular Carcinoma Cells

Abstract: Autophagy is closely related to the growth and drug resistance of cancer cells, and autophagy related 4B (ATG4B) performs a crucial role in the process of autophagy. The long non-coding RNA (lncRNA) colorectal neoplasia differentially expressed (CRNDE) promotes the progression of hepatocellular carcinoma (HCC), but it is unclear whether the tumor-promoting effect of CRNDE is associated with the regulation of ATG4B and autophagy. Herein, we for the first time demonstrated that CRNDE triggered autophagy via upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…The mechanisms underlying sorafenib resistance remain to be established. Here, we have demonstrated an oncogenic role of CRNDE in sorafenib resistance of HCC, consistent with previous reports [ 13 ]. In our experiments, CRNDE was upregulated in HCC tumor specimens and induced elevation of EGFR expression, thereby increasing proliferation and sorafenib resistance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mechanisms underlying sorafenib resistance remain to be established. Here, we have demonstrated an oncogenic role of CRNDE in sorafenib resistance of HCC, consistent with previous reports [ 13 ]. In our experiments, CRNDE was upregulated in HCC tumor specimens and induced elevation of EGFR expression, thereby increasing proliferation and sorafenib resistance.…”
Section: Discussionsupporting
confidence: 93%
“…CRNDE has been shown to act as an oncogene promoting tumor proliferation, invasion, migration, and drug resistance in multiple cancer types, including HCC [ 9 12 ]. A recent study showed that CRNDE induces sorafenib resistance in HCC by triggering autophagy via upregulation of ATG4B [ 13 ]. Additionally, CRNDE is reported to inhibit CELF2 and LATS2 expression and promote HCC proliferation, migration, and chemoresistance through epigenetic interactions with EZH2, a key component of the PRC2 complex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CRNDE is involved in the initiation and tumorigenesis of several cancers. For example, it promotes atg4b-mediated autophagy and attenuates sorafenib sensitivity in hepatocellular carcinoma cells ( Chen et al, 2021 ); it regulates eIF4A3/MUC1/EGFR signalling and modulates the response of EGFR-mutant lung cancer to EGFR tyrosine kinase inhibitor resistance ( Takahashi et al, 2021 ). In addition, CRNDE expression is modulated via DNA methylation, and CRNDE exhibits protective effects on CLL by preventing CLL progression through the miR-28/NDRG2 axis ( Ni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chen et al found that CRNDE triggered autophagy in HepG2 and Hep3B cells by increasing ATG4B levels via sponging miR-543. CRNDE silencing enhanced the sorafenib sensitivity of HepG2 and Hep3B cells, indicating that CRNDE may promote sorafenib resistance in HCC by driving ATG4B-mediated autophagy (193). Highmobility group box 1 (HMGB1) is a classical non-histone protein closely associated with autophagy (194).…”
Section: Lncrnas Control the Cellular Death Pathways In Cancer Drug R...mentioning
confidence: 99%